2002
DOI: 10.1111/j.1471-0528.2002.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Are some perinatal deaths in immigrant groups linked to suboptimal perinatal care services?

Abstract: Objective To test the hypothesis that suboptimal factors in perinatal care services resulting in perinatal deaths were more common among immigrant mothers from the Horn of Africa, when compared with Swedish mothers. Design A perinatal audit, comparing cases of perinatal deaths among children of African immigrants residing in Sweden, with a stratified sample of cases among native Swedish women. Population and setting Sixty‐three cases of perinatal deaths among immigrant east African women deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(74 citation statements)
references
References 14 publications
2
70
1
1
Order By: Relevance
“…An increased risk of suboptimal pregnancy care in ethnic minority groups has been found in previous studies. 24,25 Almost all health care services in Denmark are free of charge for all residents, and all women irrespective of ethnic origin should have free access to prenatal care at any hospital. Despite this, a recent Danish study 26 found lower attendance rates at free preventive child care examinations among immigrant children, an unfortunate trend that may also be present in the use of antenatal care among immigrant women.…”
Section: Discussionmentioning
confidence: 99%
“…An increased risk of suboptimal pregnancy care in ethnic minority groups has been found in previous studies. 24,25 Almost all health care services in Denmark are free of charge for all residents, and all women irrespective of ethnic origin should have free access to prenatal care at any hospital. Despite this, a recent Danish study 26 found lower attendance rates at free preventive child care examinations among immigrant children, an unfortunate trend that may also be present in the use of antenatal care among immigrant women.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-optimal factors in obstetric care were often likely to result in perinatal death in this immigrant group [15]. However, circumcision per se was not found to be directly related to perinatal death [16].…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis and hepatic failure (Cases 1 and 4) are potential causes of deaths that European doctors are not trained to recognise, raising the issues of suboptimal care and miscommunication. 11 In Sweden, deaths in pregnancy related to tuberculosis have not occurred for the last 50 years. The embolism-related death (Case 8) was mentioned in a recent study of maternal death and pulmonary embolism: ''Two women were immigrants from sub-Saharan Africa; there was a delay in seeking health care in one case, and verbal miscommunication might have contributed in both cases. ''…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] A recent confidential enquiry into maternal deaths in the UK studied deaths among disadvantaged women, including black African women, and found they were more likely to die during pregnancy, childbirth or the puerperium than their white counterparts. 12 To our knowledge, there is a lack of similar studies of maternal mortality and ethnicity in Sweden.…”
mentioning
confidence: 99%